Alfabetizando os filhos da rainha para a civilidade/modernidade: o Instituto Pedagógico em Campina Grande-PB (1919-1942) - Andrade, Vivian Galdino de (2014)
The thesis discusses the role redeemed by a school institution and their subjects in the project of modernization of Campina Grande city, during the years from 1919 to 1942. Our aim is to present the school as one of the institutions responsible for generating in the city a modern sensibility, educating and civilizing the subject to the casts of a city in "progress". The Pedagogical Institute, focus of our discussion, was the first private school in the city referenced with "a pedagogical modernity" that was alphabetizing gand professionalized the subject. Had as Director Lt. Alfredo Dantas and worked at primary and secondary level, but also with the contribution of Attached Schools (Escola Normal João Pessoa, Escola Militar General Pamplona e Escola de Comércio e Peritos Contadores) that had as a guiding principle to educate citizens to meet the economic and commercial needs that arose in the city. Sanitation, electricity, literacy, trade development, health and urbanization were the principles motivating a project of a modern city, which led several institutions and social subjects in Brazil to experience a Pedagogy of the City. Through readings of authors such as Norbert Elias e Michel Foucault, we problematize this intense relationship between the school, the city and individuals, in order to point out an education that grew back and produced citizens able to modern living. It was through the New Cultural History and apprehension/reflection of journalistic sources and printed educational produced by the Institution itself that we trace the possible paths to be set for the preparation of this text, whishing the production of a cartography of the history of the Pedagogical Institute, denoting how this educational institution was at the service of the city, but also of the homeland. School institution, school culture (material), discipline and civilization are our motto concepts of reflection, that point in their interstices to a discussion on school architecture, the teaching materials, teachers and pedagogical forms as sources that remember the organization s school life of the students from the Pedagogical Institute. To assist us in this discussion we employed a group of authors from the historiography of Education, among them Luciano Faria Filho, Clarice Nunes, Tarcisio Vago, Cynthia Greive Veiga, Dermeval Saviani and more, aiming to discuss the culture of school space itself in connection with the history of the city, which taught/had civilized bodies and minds, schooling the sensitivities of the subject